PERSEPSI KONSUMEN TERHADAP CITRA ”PASAR TRADISIONAL RATU TUNGGAL” DI KOTA PANGKALPINANG - Yulia, Yulia; Hanifah, Rahmah; Setiawan, Iwan (Program Studi Magister Ilmu Pertanian, Fakultas Pertanian, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2024)
This study aims to describe consumer perceptions of image in the market and describe the level of consumer perceptions of price, service, product quality and physical environment on consumer satisfaction in the Ratu Tunggal traditional market in Pangkalpinang city. The research method used is the survey method. The sampling method used is Accidental Sampling with a sample size of 100 consumers. The data analysis method uses descriptive qualitative using a Likert scale. The results showed that the price of the products offered varied, affordable, cheaper than modern markets with appropriate quality. The services provided are personal, polite, friendly and patient and provide a comfortable atmosphere so that consumers are comfortable shopping. The quality of the products is diverse, not inferior in quality to the modern market and the prices offered are comparable, has a parking lot, several parking attendants, public toilets, and has large buildings that can be rented out. Then the level of consumer perception of the satisfaction of prices, services, product quality and the physical environment in Pasar Ratu Tunggal is very satisfied